Islamic Currency Swap: Can Be The Best Way to Hedge Indonesia Hajj Fund? - Irvan Maulana; Muhammad Rafdi (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2018)
The operational costs of Hajj in foreign currencies will always face the risk of changes in exchange rates. Hajj operational costs will continue to grow in line with the increasing number of pilgrims. But at present, the government (BPKH) does not have a currency hedging policy to reduce the risk of fluctuating currency values. Hajj operational costs are saved in rupiah, dollar and riyal currencies. As a result, deposits of pilgrims will continue to be overshadowed by the reduction in value due to the depreciation of the rupiah against the dollar and riyals. Hedging policy is a necessity in the management of Hajj funds. This study will use an Islamic currency swap simulation analysis. According to the MUI DSN No 96 in 2015, a swap is a contract that starts a spot transaction followed by a forward agreement by setting a forward exchange rate. Then it is settled by spot transactions using the agreed forward exchange rate. The results of the study show that the dollar and riyal in 2018 are in a state of high volatility, so hedging is needed to reduce cash outflows. Based on analysis, Islamic currency swap can be the best hedging to the operational costs of Hajj in USD is with tenors 30 days, 180 days, 360 days. while the operational costs of Hajj are in Saudi Arabia Riyal currency, efficient in overnight tenors, 30 days, 90 days and 180 days.